Polymorphisms of HSP70 genes are involved in the pathogenesis of idiopathic inflammatory myopathy - Tana Svitalkova; Antonin Ambroz; Marketa Svetla; Martina Misunova; Libor Kolesar; Peter Novota (Rheumatology)
Introduction Idiopathic inflammatory myopathies (IIM) are a group of rare systemic autoimmune diseases characterized by muscle weakness, histopathological signs of inflammation in muscle tissues, elevated serum levels of muscle-associated enzymes, inflammatory mononuclear cells infiltrating muscle tissue and progressive symmetrical proximal muscle weakness. The current view is that they begin by immune activation in response to environmental factors in genetically predisposed people, but despite the number of investigations into the genetic background, the detailed etiopathogenesis remains unknown. The aim of this study was to examine the relationship between select polymorphisms located in the human major histocompatibility complex (MHC) and IIM. These genetic markers may take part in the onset of the autoimmune process, and their identification could aid in the diagnosis and classification of IIM subtypes.